ANTIBACTERIAL ACTIVITY OF LOCAL MALAYSIAN HONEY - NURIZA TUMIN; N. ARSYIAH A. HALIM; M. SHAHJAHAN; NOOR IZANI N. J.; MUNAVVAR A . SATTAR; ABDUL HYE KHAN; S. S. J. MOHSIN (Malaysian Journal of Pharmaceutical Sciences, 2005)
The antibacterial activity of five different local honey brands viz. Tualang, Hutan, Gelang, Pucuk Daun and Ee Feng Gu honey obtained from different locations in Malaysia was investigated. Honeys were tested for putative antibacterial activity by disc diffusion assay and their inhibition of growth of six pathogenic bacteria in batch culture. Minimum inhibitory concentration (MIC) was determined for each of the honey tested using standard assay procedures. In terms of physicochemical properties, it was observed that the pH of these honeys was within 3.55–4.91, their specific gravity was 1.3–1.35, moisture content was 16–23.3% and dry matter content was 76.6–84%. Marked variations were observed in the antibacterial activity of these honey samples. Two honey brands, Hutan and Gelang did not produce any substantial antibacterial activity while other brands showed a spectrum of antibacterial activity with their growth inhibitory effect against at least three-four different bacterial species including S. typhi, S. aureus, S. sonnie and E. coli.